2020
DOI: 10.1590/s0004-2803.202000000-54
|View full text |Cite
|
Sign up to set email alerts
|

Oral Rutin Suspension Intervene in Hepatic Hyperplasia in Rats

Abstract: BACKGROUND: Rutin is a flavonol glycoside that can be found in a wide variety of vegetables and has activity, anti-cancer, anti-inflammatory and anti-diabetic properties. OBJECTIVE: This study investigated the effect of rutin oral administration on Wistar rats submitted to hepatic hyperplasia after partial hepatectomy (PH). METHODS: To achieve this, we considered the analysis of hepatic hyperplastic and plasma biochemical activity of Wistar rats, subjected to treatment with rutin 40 mg/kg/day for 10 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The antiproliferative activity of herbal medicines provides hope for treating cancer, tumors, and other malignant diseases. T. chinensis contains various anticancer compounds such as rutin, quercetin, and phlorin [ 70 72 ]. Park et al found that 70% ethanol extracts of T. chinensis (25–100 μg/mL) inhibited human colorectal cancer cell growth in a dose-dependent manner.…”
Section: Anticancer Effectmentioning
confidence: 99%
“…The antiproliferative activity of herbal medicines provides hope for treating cancer, tumors, and other malignant diseases. T. chinensis contains various anticancer compounds such as rutin, quercetin, and phlorin [ 70 72 ]. Park et al found that 70% ethanol extracts of T. chinensis (25–100 μg/mL) inhibited human colorectal cancer cell growth in a dose-dependent manner.…”
Section: Anticancer Effectmentioning
confidence: 99%